2004
DOI: 10.1038/modpathol.3800118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epidermal growth factor receptor and activated epidermal growth factor receptor expression in pituitary adenomas and carcinomas

Abstract: Epidermal growth factor receptor plays an important role in the pathogenesis of many malignancies. Various growth factors, including epidermal growth factor receptor, have been shown to influence pituitary tumor growth and differentiation. To analyze the role of epidermal growth factor receptor in pituitary tumor development, we examined normal pituitaries (n ¼ 8), pituitary adenomas (n ¼ 158), and pituitary carcinomas (n ¼ 7) for expression of epidermal growth factor receptor protein and messenger RNA using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 32 publications
2
40
1
Order By: Relevance
“…This is indicated by the presence of immunoreactivity for the phosphorylated, i.e., activated, receptor in these tumors (41,52). EGFR-expressing corticotrophinomas also had very weak or absent immunoreactivity for the cell cycle inhibitor p27 (41).…”
Section: Egfr and Corticotroph Functionmentioning
confidence: 99%
“…This is indicated by the presence of immunoreactivity for the phosphorylated, i.e., activated, receptor in these tumors (41,52). EGFR-expressing corticotrophinomas also had very weak or absent immunoreactivity for the cell cycle inhibitor p27 (41).…”
Section: Egfr and Corticotroph Functionmentioning
confidence: 99%
“…Several studies have found the expression of EGF and/or EGFR in pituitary adenomas, sometimes associated with a more aggressive (invasive) phenotype (Lubke et al 1995, LeRiche et al 1996, Asa & Ezzat 2002, Onguru et al 2004, Cooper et al 2011, Fukuoka et al 2011, del Pliego et al 2013. In ACP, EGF signaling has been reported to play a role in tumor cell migration (Hölsken et al 2011).…”
Section: Dysregulation Of Egf/fgf In Pituitary Tumorigenesismentioning
confidence: 99%
“…9 Immunostaining for insulin, glucagon, gastrin and somatostatin was performed as previously reported.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Various studies have shown that EGFR is expressed in carcinoids and pancreatic endocrine tumors. [4][5][6][7][8] However, the activated or phosphorylated form of EGFR (P-EGFR) has been examined in only a few neuroendocrine tumors, 9 and it has not been studied in primary gastrointestinal carcinoid or pancreatic endocrine tumors.…”
mentioning
confidence: 99%